2013
DOI: 10.1002/ana.23868
|View full text |Cite
|
Sign up to set email alerts
|

G protein–coupled receptor kinase 2 and group I metabotropic glutamate receptors mediate inflammation‐induced sensitization to excitotoxic neurodegeneration

Abstract: Objectives The concept of inflammation-induced sensitization is emerging in the field of perinatal brain injury, stroke, Alzheimer disease and multiple sclerosis. However, mechanisms underpinning this process remain unidentified. Methods We combined in vivo systemic lipopolysaccharide (LPS) or Interleukin-1β (IL-1β) induced sensitization of neonatal and adult rodent cortical neurons to excitotoxic neurodegeneration with in vitro IL-1β sensitization of human and rodent neurons to excitotoxic neurodegeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…pression of IL-23 (a key factor for T H 17 cell differentiation), TNF␣, and iNOS mRNA (Ghoreschi et al, 2010). This analysis showed that neither pFTY720 nor S1P (up to 10 M) suppressed microglial activation directly (Fig.…”
Section: Fty720 Lacks Direct Inhibitory Effects On Microgliamentioning
confidence: 85%
See 3 more Smart Citations
“…pression of IL-23 (a key factor for T H 17 cell differentiation), TNF␣, and iNOS mRNA (Ghoreschi et al, 2010). This analysis showed that neither pFTY720 nor S1P (up to 10 M) suppressed microglial activation directly (Fig.…”
Section: Fty720 Lacks Direct Inhibitory Effects On Microgliamentioning
confidence: 85%
“…Growing evidence indicates that perinatal inflammation exacerbates HI and excitotoxic lesions, causing greater brain damage in neonates (Dommergues et al, 2000;Dammann et al, 2002;Degos et al, 2013). Consequently, preclinical and clinical studies both indicate that inflammation-sensitized HI brain injury is less responsive to therapeutic hypothermia than pure-HI injury in neonates (Wintermark et al, 2010;Osredkar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it has been reported that activation of kainite receptors by culturing oligodendrocytes with as little as 10 μM glutamate sensitizes the oligodendrocytes to complement attack and lysis (Alberdi et al, 2006). Glutamate levels are increased in CNS lesions during MS (Pitt et al, 2003;Pampliega et al, 2011) and other CNS inflammatory situations (Erhardt et al, 2013;Degos et al, 2013). Therefore, it might be expected that oligodendrocytes in or near inflammatory loci could become more sensitized to antibody mediated attack than oligodendrocytes in other parts of the brain.…”
Section: Principal Findings Of the Thesismentioning
confidence: 99%